2018
DOI: 10.1167/iovs.18-24037
|View full text |Cite|
|
Sign up to set email alerts
|

Differential Distribution of Laminin N-Terminus α31 Across the Ocular Surface: Implications for Corneal Wound Repair

Abstract: PURPOSE. Laminin N-terminus (LaNt) a31 is a relatively unstudied protein derived from the laminin a3 gene but structurally similar to netrins. LaNt a31 has, to date, been investigated only in two-dimensional (2D) keratinocyte culture where it influences cell migration and adhesion, processes integral to wound repair. Here we investigated LaNt a31 distribution in ocular surface epithelium, during limbal stem cell activation, and corneal wound healing.METHODS. Human, mouse, and pig eyes, ex vivo limbal explant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 56 publications
6
42
0
Order By: Relevance
“…Previously, we reported that increased expression of LaNt α31 led to increased cell spreading and reduced migration of primary limbal-derived corneal epithelial cells (Barrera et al, 2018) . To investigate the mechanism for these effects we turned to the widely-used and well characterised limbal-derived corneal epithelial cell line hTCEpi (Yamamoto et al, 2005;Dreier et al, 2012;Yanez-Soto et al, 2015;Hampel et al, 2018;Kaplan et al, 2019) (Supplemental Figure 1A) and used the same adenoviral construct to drive expression of LaNt α31 with a C-terminal eGFP tag (hereafter +LaNt α31, Figure 1B), comparing results against cells expressing eGFP alone (+eGFP).…”
Section: High Lant α31 Expression Curtails Epithelial Keratinocyte MImentioning
confidence: 92%
See 4 more Smart Citations
“…Previously, we reported that increased expression of LaNt α31 led to increased cell spreading and reduced migration of primary limbal-derived corneal epithelial cells (Barrera et al, 2018) . To investigate the mechanism for these effects we turned to the widely-used and well characterised limbal-derived corneal epithelial cell line hTCEpi (Yamamoto et al, 2005;Dreier et al, 2012;Yanez-Soto et al, 2015;Hampel et al, 2018;Kaplan et al, 2019) (Supplemental Figure 1A) and used the same adenoviral construct to drive expression of LaNt α31 with a C-terminal eGFP tag (hereafter +LaNt α31, Figure 1B), comparing results against cells expressing eGFP alone (+eGFP).…”
Section: High Lant α31 Expression Curtails Epithelial Keratinocyte MImentioning
confidence: 92%
“…Mouse monoclonal antibodies for IF against LMα3 (clone RG13) (Gonzales et al, 1999) used at 10 μg/ml, rabbit polyclonal antibodies raised against LM332 (J18) (Hopkinson et al, 1992) and cytokeratin 12 {Kurpakus, 1990 #12636} were used at 1:50, and human monoclonal antibodies to BPAG1e (5E) (Hashimoto et al, 1993) used at 1:2, were generous gifts from Jonathan Jones, Washington State University, WA. Mouse monoclonal antibodies raised against human LaNt α31 (clone 3E11) used at 1.9 μg/ml for IB were described previously (Barrera et al, 2018;Troughton et al, 2020a). Rat monoclonal antibodies raised against LMγ1 (clone A5, ab80580) used at 1 μg/ml, and mouse monoclonal antibodies raised against LMβ2 (clone CL2979) used at 1 μg/ml were from Abcam.…”
Section: Antibodies and Other Reagentsmentioning
confidence: 99%
See 3 more Smart Citations